Association of Micro RNA in Multiple Sclerosis Patients - Hiba Amar malallah; Fadyia Mahdi Alameedy (European Science Publishing, 2024)
Multiple sclerosis (MS) is a chronic condition characterised by immune system involvement and is the primary contributor to disability in the young adult population. Post-transcriptional regulation of gene expression is largely dependent on microRNAs (miRNAs). In the context of multiple sclerosis, miR-155 is one of these variables that plays a critical role in the regulation of inflammatory processes and the modulation of the autoimmune response. In inflammatory conditions, MiR-155 plays a role in the breakdown of the blood-brain barrier (BBB) by down-regulating key junctional proteins. Demyelination is facilitated by a number of processes, including the activation of microglia, the polarization of astrocytes, the down-regulation of CD47 protein, and the manipulation of key transcription factors. Since miR-155 indirectly affects the development of regulatory T (Treg) cells, which are essential in reducing pain hypersensitivity, it plays an important role in the etiology of neuropathic pain. In addition, this analysis looked at how MS-related symptoms develop in response to disease-related stresses, brain atrophy, and pro-inflammatory factors. Recent studies have shed light on miR-155's role in controlling stress, anxiety, hippocampal inflammation, and treatment-resistant depression. Reducing miR-155 expression has been shown to be an effective strategy for halting the pathophysiological processes that lead to multiple sclerosis (MS). The purpose of this review was to better understand the wide-ranging effects of miR-155 dysregulation on the pathophysiology of MS and to highlight possible future research avenues.
Keywords: Micro RNA , Multiple sclerosis (M.S) , CNS.